2020
DOI: 10.15520/jcmro.v3i01.253
|View full text |Cite
|
Sign up to set email alerts
|

Connaissances De L’hypertension Arterielle Et De Ses Complications Au Centre Hospitalier De Soavinandriana

Abstract: Introduction : A Madagascar, on assiste actuellement à une nette augmentation de la prévalence de l'hypertension artérielle (HTA)et de ses complications. Le but de cette étudeétait d’évaluer le niveau de connaissances des patients hypertendus en matière d’HTA,de connaitre le terme HTA et ses complications ainsi que la valeur tensionnelle cible sous traitement avant l’éducation thérapeutique. Méthodes : Nous avons mené une étude transversale et descriptive des patients hypertendus vus au centre hospitalie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, such studies typically focus on high-pressure patients, and most often in a hospital setting. A hospital-based study in Madagascar found that 80.92% of participants were knowledgeable [10]. Another study of hypertensive patients carried out by the Association for Medical Assistance to Older People "KAFOLI" in Burkina Faso reported that 68% of patients had good knowledge [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such studies typically focus on high-pressure patients, and most often in a hospital setting. A hospital-based study in Madagascar found that 80.92% of participants were knowledgeable [10]. Another study of hypertensive patients carried out by the Association for Medical Assistance to Older People "KAFOLI" in Burkina Faso reported that 68% of patients had good knowledge [7].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge gaps present formidable barriers to the efficient prevention and treatment of Hypertension [12,13]. Enhancing patient understanding of Hypertension can facilitate better blood pressure management, reduce cardiovascular complication risks, and improve adherence to antihypertensive treatments [10]. Moreover, addressing modifiable behavioural risk factors such as unhealthy diets, smoking, excessive alcohol consumption, and physical inactivity is vital for hypertension prevention.…”
Section: Introductionmentioning
confidence: 99%